Biochemical stages of amyloid-β peptide aggregation and accumulation in the human brain and their association with symptomatic and pathologically preclinical Alzheimer’s disease - Rijal Upadhaya, Ajeet; Kosterin, Irina; Kumar, Sathish; von Arnim, Christine A. F.; Yamaguchi, Haruyasu; Fändrich, Marcus; Walter, Jochen; Thal, Dietmar Rudolf (Brain (London, England : 1878), 2014)
Alzheimer's disease is characterized by the deposition of amyloid-β peptide in the brain. N-terminal truncation resulting in the formation of AβN3pE and phosphorylation at serine 8 have been reported to modify aggregation properties of amyloid-β. Biochemically, soluble, dispersible, membrane-associated, and insoluble, plaque-associated amyloid-β aggregates have been distinguished. Soluble and dispersible amyloid-β aggregates are both in mixture with the extracellular or intracellular fluid but dispersible aggregates can be cleared from proteins in solution by ultracentrifugation. To clarify the role of phosphorylated amyloid-β and AβN3pE in soluble, dispersible, membrane-associated, and plaque-associated amyloid-β aggregates in the pathogenesis of Alzheimer's disease we studied brains from 21 cases with symptomatic Alzheimer's disease, 33 pathologically preclinical Alzheimer's disease cases, and 20 control cases. Western blot analysis showed that soluble, dispersible, membrane-associated and plaque-associated amyloid-β aggregates in the earliest preclinical stage of Alzheimer's disease did not exhibit detectable amounts of AβN3pE and phosphorylated amyloid-β. This stage was referred to as biochemical stage 1 of amyloid-β aggregation and accumulation. In biochemical amyloid-β stage 2, AβN3pE was additionally found whereas phosphorylated amyloid-β was restricted to biochemical amyloid-β stage 3, the last stage of amyloid-β aggregation. Phosphorylated amyloid-β was seen in the dispersible, membrane-associated, and plaque-associated fraction. All cases with symptomatic Alzheimer's disease in our sample fulfilled biochemical amyloid-β stage 3 criteria, i.e. detection of phosphorylated amyloid-β. Most, but not all, cases with pathologically preclinical Alzheimer's disease had biochemical amyloid-β stages 1 or 2. Immunohistochemistry confirmed the hierarchical occurrence of amyloid-β, AβN3pE, and phosphorylated amyloid-β in amyloid plaques. Phosphorylated amyloid-β containing plaques were, thereby, seen in all symptomatic cases with Alzheimer's disease but only in a few non-demented control subjects. The biochemical amyloid-β stages correlated with the expansion of amyloid-β plaque deposition and with that of neurofibrillary tangle pathology. Taken together, we demonstrate that AβN3pE and phosphorylated amyloid-β are not only detectable in plaques, but also in soluble and dispersible amyloid-β aggregates outside of plaques. They occur in a hierarchical sequence that allows the distinction of three stages. In light of our findings, it is tempting to speculate that this hierarchical, biochemical sequence of amyloid-β aggregation and accumulation is related to disease progression and may be relevant for an increasing toxicity of amyloid-β aggregates.